Purpura Fulminans with Peripheral Gangrene in severe Falciparum Malaria: a case series (2019)
Background: Purpura fulminans is an acute fatal illness consisting of septicaemia, shock, and disseminated intravascular coagulation, often manifesting with gangrene of the distal extremities and necrosis of skin. Purpura fulminans associated with severe malaria has rarely been reported among children. Case Report: Two cases of purpura fulminans with disseminated intravascular coagulation probably due to severe falciparum malaria, are presented from a tertiary health facility in Nigeria. Both cases were males, and were infants aged 6 and 7 months respectively. They presented with fever, seizures, loss of consciousness and features of shock and had associated peripheral gangrene which developed hours into admission. Investigations showed P. falciparum hyper-parasitemia and evidence of disseminated intravascular coagulation. No focus for sepsis was identified and there were no bacterial isolates from blood culture. The second child survived but was left with amputated digits and audiovisual deficits. Conclusion: The cases presented demonstrate that purpura fulminans can occur in children with severe malaria even in P. falciparum endemic settings.